Endoscopic features of gastric mucosa in children having pathohistological evidence of Helicobacter pylori infection - Tomić, Teo (Array, 2009)
Summary: Infection with Helicobacter pylori (Hp) is common in children from developing countries, particularly in adolescents. It is associated with chronic gastritis and stomach cancer. A characteristic endoscopic finding in children is nodular gastritis. The aim of this study was to assess and confirm association of nodular gastritis, mainly of anthral mucosa, with Hp infection in children. A total of 195 children 1 to 15 years of age were studied during a two-year period (2004–2006). There were 107 girls (54.9%) and 88 boys (45.1%). The patients presented with recurrent epigastric pain, nausea, vomiting, heartburn, sour mouth, regurgitation, bloating or other dyspeptic symptoms. The complaints were recorded by a structured interview with parents and older children. Upper endoscopy was performed in all children. The presence and degree of mucosal granulation was recorded and two samples of mucousa from the antrum and the small curvature were taken. Biopsy material was processed for histology as usual, stained with 2% Giemsa and examined by a pathologist for the presence of Hp. A total of 40 of 195 children (20.5%) have had positive Hp infection and a 27 of 40 (67.5%) have had a granular aspect of anthral mucosa at the endoscopy. Sensitivity of the finding was 87.5%, specificity 93.5%, positive predictive value 73%, negative predictive value 91.8%, p<0.05. Average age of those patients was 11.5±3.0 years. Subjective symptoms of dyspepsia (as recorded by the questionnaire) were often associated with Hp positivity, but short of statistical significance. No difference between boys and girls was noted. Endoscopic finding of nodular gastritis, especially in areas of antrum and small curvature, showed a highly positive correlation with Hp infection